The Philippine Bare-Backed Fruit Bat Dobsonia Chapmanirabor, 1952: Rediscovery and Conservation Status on Cebu Island - Pagunutalan, Lisa Marie J.; Pedegrosa, Marisol; Gadiana, Mery Jean C. (Silliman Journal, 2022)
The Philippine bare-backed fruit bat Dobsonia chapmani is the largest cave-roosting bat in the Philippines. Known only from the islands of Cebu and Negros, it was also the first mammal declared extinct in the Philippines not having been recorded on either of these islands since the early 1970s, despite systemic searches by trained researchers (Heaney et. al., 1998; Heaney & Regalado, 1998). However, a preliminary survey conducted in Mabuli, Carmen, Cebu in late February 2001 resulted in the unexpected mist-netting of several individuals of this species, all of which were released after being measured and photographed. Along with the site of rediscovery of this species on Negros in 2003 (Alcala et al., this volume), the forest in Carmen and Catmon constitutes one of the species' last and critically important strongholds. However, the only available habitat in this area is a series of small secondary growth, limestone forest fragments, all of which are highly disturbed. The largest remaining fragment, circa 60 ha, is also threatened by the cutting of trees for charcoal, agricultural development, and poaching. In addition, the site is not a protected area and was not included in the listing of 'Key Conservation Sites' on Cebu (Mallari et. al, 2001). Thus, it is important to identify and implement conservation measures in order to protect the surviving populations of this once believed extinct, but still critically endangered, endemic fruit bat.